2022
DOI: 10.1002/viw.20210008
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic nanoprobes for biological hydrogen sulfide detection and imaging

Abstract: Hydrogen sulfide (H2S) is a gaseous molecule involved in multiple biological and physiological processes, including various diseases such as cancer and neurodegenerative disorders. This has led to the development of various analytical methods to monitor H2S in biological settings. Among these, fluorescence‐based assays, specifically organic small‐molecule probes, have been thoroughly utilized. They offer good sensitivity and specificity as sensors, and noninvasive detection with high spatiotemporal resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 229 publications
0
10
0
Order By: Relevance
“…For example, the o -diamino aromatic moiety is a recognition group for NO, and the cyclization reaction of o -diamine with NO produces a triazole moiety, which alters the electronic property and conjugation nature [ 159 , 160 , 161 ]. For H 2 S detection, the popularly used approaches include reduction of azides into amines and nucleophilic addition of H 2 S to the electrophilic group [ 162 , 163 ]. Some representative AIEgens for sensing gasotransmitters are listed Figure 13 , which show great potential for applications in biological imaging and disease diagnosis.…”
Section: Detection Of Gasotransmittersmentioning
confidence: 99%
“…For example, the o -diamino aromatic moiety is a recognition group for NO, and the cyclization reaction of o -diamine with NO produces a triazole moiety, which alters the electronic property and conjugation nature [ 159 , 160 , 161 ]. For H 2 S detection, the popularly used approaches include reduction of azides into amines and nucleophilic addition of H 2 S to the electrophilic group [ 162 , 163 ]. Some representative AIEgens for sensing gasotransmitters are listed Figure 13 , which show great potential for applications in biological imaging and disease diagnosis.…”
Section: Detection Of Gasotransmittersmentioning
confidence: 99%
“…For example, an explanation for the dual emission in Au 28 (SG) 16 NCs (corrected as Au 25 in later works) could be presented after Link et al proposed their energy band structure by considering the solid-state model and molecular model for the origin of the two luminescence bands in Au 28 (SG) 16 NCs. 102 It was reported that both the radiative intraband transition (sp-sp) and the radiative interband recombination (sp-d) in the HOMO-LUMO gap contribute to the low and high energy luminescence bands, respectively.…”
Section: Key and Influencing Factors For The Origin Of Luminescence I...mentioning
confidence: 99%
“…The advantages and disadvantages of organic fluorophores vs. metal-based nanoclusters are summarized in Table 1. [15][16][17][18] Hence, recently, review articles and perspectives on metal-based nanomaterials have attracted significant attention for a wide range of applications. [19][20][21][22][23][24][25][26][27][28] Among the applications of metalbased NPs, hypoxic tumor radiotherapy is one of the most important for clinical cancer treatment.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] At present, various ingenious healthcare devices have been explored for detecting body temperature, blood pressure, heart rate and glucose based on thermoelectric effect, piezoelectric/piezoresistive mechanism, capacitive effect, or electrocatalytic/electrochemical principles. [18][19][20][21][22][23][24] Significantly, these monitoring devices can be integrated into wearable clothes or watches for continuous healthcare, which makes home-based telehealth monitoring available. [25][26][27] Therefore, to further promote the development of wearable health monitoring devices and their medical applications, this mini-review centers on the latest progress of wearable skin-like sensing devices and their applications in health monitoring, aiming to offer a panoramic review from the perspectives of health monitoring fundamentals, device construction, potential clinical applications and future outlook.…”
Section: Introductionmentioning
confidence: 99%